Gender equality in sports : the gender pay gap and women's representation in Icelandic sports clubs - Helena Jónsdóttir 1994- (2021)
Lokaverkefni í tvíþættri gráðu í íþróttafræði og íþróttastjórnun við Háskólann í Reykjavík og Molde University, Noregi. Research questions: The study aimed to analyze if there was a gender pay gap in Icelandic sports, and if so, examine to what extent the gap was. Furthermore, the aim was to analyze how Icelandic sports clubs accomplish gender equality in their daily operations. Research methods: Two separate studies were conducted. An online questionnaire asking about the salary, bonuses and benefits was sent to players playing in men’s and women’s top divisions in basketball, football and handball in Iceland. 255 players answered the questionnaire; 162 women and 125 men. An online questionnaire asking about women in sports boards and the actions taken in terms of gender equality was sent to CEO’s of all Icelandic sports clubs that have both men’s and women’s team in at least one of these three sports: basketball, football or handball (N=35). In total, 15 CEO’s answered the questionnaire. Results and findings: The results show that male athletes earn more than female athletes in Iceland. There was significant difference in salary between the sexes in football, but not in basketball and handball. Moreover, the results show that women are not underrepresented in decision making in Icelandic sports. However, the majority of those holding the position of chairman are men while women are most likely to be secretaries. Although Icelandic sports clubs systematically aim to involve women in the process shaping women’s sports, they appear to distribute a lower share of their finances to their women’s teams. Tilgangur: Markmið rannsóknarinnar var að skoða hvort kynbundinn launamunur væri til staðar í íþróttum á Íslandi. Þá var einnig markmiðið að skoða hvernig íslensk íþróttafélög ná fram jafnrétti kynjanna í þeirra daglega starfi. Aðferð: Tvennskonar rannsóknir voru framkvæmdar þar sem rafrænir spurningalistar voru sendir á þátttakendur. Fyrri spurningalistinn var sendur á alla leikmenn í efstu deildum karla og ...